On the energy efficiency of hydrogen production processes via steam reforming using membrane reactors. (8th January 2019) - Bruni, G.; Rizzello, C.; Santucci, A.; Alique, D.; Incelli, M.; Tosti, S.
Abstract: The novel paradigm of distributed energy production foresees the production of hydrogen from methane and biomasses in small plants, which may take advantage from membrane-based processes. By means of a modeling approach, this paper compares the energy efficiency of two membrane-based processes to produce H2 from methane steam reforming. The two-step process (TS) envisages a high temperature classical reactor and a following WGS stage in a membrane reactor, while the alternative process uses a simple packed-bed membrane reactor (MR). Both processes show a general increase of H2 production and energy efficiency with the pressure and a maximum energy efficiency for S/C of 4, while the increase of the space velocity reduces the performances of the MR. The results show that the TS process performs better than the studied MR and that the maximum energy efficiency of both processes is between 30 and 40%. A comparison with the literature shows that the TS process may achieve similar performances respect to an intensified MR. Highlights: Two membrane processes for H2 production via methane steam reforming are studied. The reforming is assessed at T = 650–900 °C, P = 3–15 bar, S/C = 3–12. Maximum hydrogen yield reaches 80%; Energy efficiency is between 30% and 39%. Two-Step process generally performs better than packed bed membrane reactor. Results agree with experimental and modeling studies from literature.